2004
DOI: 10.1111/j.1365-2516.2004.00928.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis of patients with haemophilia at the International Haemophilia Training Centre, Bangkok, Thailand

Abstract: Haemophiliac treatment in less developed countries is limited to locally prepared fresh frozen plasma, cryoprecipitate, cryo-removed plasma and lyophilized products as replacement therapy. Factor concentrate is seldom used because of the high price. The present study reports the survival analysis of 164 patients comprising 138 haemophilia A and 26 haemophilia B cases from 134 families registered at the International Haemophilia Training Centre-Bangkok, Faculty of Medicine, Ramathibodi Hospital, Mahidol Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…The fact that it was a single‐centre study should also be considered. Similar to our study the number of severe haemophilia A patients in Chinese study were 11, although the total number of patients were 34 (28 haemophilia A and six haemophilia B) including both severe and moderate haemophilia making the study population very heterogeneous. Second major limitation was significantly higher median age and median weight in episodic group compared to prophylaxis group.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that it was a single‐centre study should also be considered. Similar to our study the number of severe haemophilia A patients in Chinese study were 11, although the total number of patients were 34 (28 haemophilia A and six haemophilia B) including both severe and moderate haemophilia making the study population very heterogeneous. Second major limitation was significantly higher median age and median weight in episodic group compared to prophylaxis group.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of comprehensive care is further exemplified by the analysis of 164 patients treated at the International Haemophilia Training Centre at Bangkok with blood and blood components from 1971 to 2000. The estimated probability of survival beyond 13 years of age of patients with severe hemophilia increased from 0.85 during the first decade of observation to 0.94 and 1 in the second and third decades (Chuansumrit et al 2004). The mortality rate fell from 30% to 14% and 5% over the three decades of observation.…”
Section: Management Of Congenital Hemophilia In the Elderlymentioning
confidence: 99%
“…[6][7][8] Nowadays, given the improvement in coagulation concentrates, the life expectancy of individuals with hemophilia appears to be equal to that of individuals without hemophilia in developed countries. [9][10][11] Furthermore, recent findings have demonstrated that prophylaxis regimens decrease bleeding, pain, the frequency and duration of hospitalizations, disability, and quality of life in the hemophiliac population. Several groups of researchers 12,13 have hypothesized that there is an obvious link between the economic capacity of a country and the availability of the coagulation factors, diagnostic facilities, patients, care levels, and death rates due to bleeding disorders.…”
Section: Introductionmentioning
confidence: 99%